Trabalho terceirizado e universidade pública: uma análise a partir da UERJ - Deise Mancebo (EccoS – Revista Científica, 2017)
The article presents the results of research that discusses the outsourced work, taking as an empirical reference the situation of the University of the State of Rio de Janeiro (UERJ). Throughout the text, the following are analyzed: (1) outsourcing and ongoing “labor reform”; (2) the impacts of the recently approved Law of Outsourcing, and (3) outsourcing in UERJ, where, after a brief characterization of the Rio de Janeiro State crisis, both methodological procedures and the main results of the investigation are exposed. In the final considerations, the possible impacts of the extension of the outsourcing to the principal activities of the public university are discussed.